Zirconium oxide nano-powder and preparation method thereof
By using anhydrous ethanol as a dispersion medium in the preparation of zirconia powder, slowly adding precipitation reaction, combined with spray drying and low-temperature calcination, the problem of colloidal particles agglomeration in the coprecipitation method is solved, and high purity and uniform particle size are achieved Preparation of zirconia nano powders.
Patent Information
- Application Number
- CN202411371518.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
AI Technical Summary
In the existing preparation methods of zirconia powder, the co-precipitation method has difficulties in the agglomeration of precursor colloid particles, and excessive surfactants are difficult to completely remove during the calcination process, and impurities may be introduced.
Using anhydrous ethanol as the dispersion medium, mixing the inorganic zirconium salt and the inorganic yttrium salt with water to form a mixed solution A, and mixing the inorganic alkaline precipitant with water and anhydrous ethanol to form a mixed solution B, and slowly add it dropwisely. The precipitation reaction was then filtration, washing, spray drying and low-temperature calcination to prepare nanozirconia powder.
It effectively solves the agglomeration problem of zirconia powder during the preparation process, avoids the introduction of impurities, improves the particle size uniformity and purity of the powder, reduces the preparation cost, and is simple and safe in the process.
Smart Images

Figure CN119409223A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of ceramic powder preparation, and in particular relates to a zirconium oxide nanopowder and a preparation method thereof. Background Art
[0002] Zirconia ceramics are widely used in ceramic cutting tools, catalyst carriers, gas sensors, solid oxide fuel cells and other fields due to their excellent physical and chemical properties. With the continuous upgrading of product performance, the performance of zirconia ceramic materials is also constantly improving, and zirconia powder plays a vital role in the performance of ceramic materials. High-purity, ultra-fine, uniformly sized zirconia powder is the key to the preparation of high-performance zirconia ceramics.
[0003] At present, there are two common methods for preparing zirconium oxide powder: solid phase and liquid phase. The solid phase method has been basically excluded by most industrial production due to its high reaction temperature and serious powder agglomeration. The liquid phase method is a commonly used method for preparing zirconium oxide nanopowders because the raw materials are mixed evenly and the powder calcination temperature is low, so the original crystal size of the prepared powder is smaller and the secondary particle agglomeration is smaller. Among them, the hydrothermal method is the most well-known, but the hydrothermal method usually requires the use of a hydrothermal reactor. High temperature and high pressure equipment undoubtedly increases the production cost in terms of equipment investment and safety maintenance. Therefore, among the wet chemical methods, the coprecipitation method is a process route with a simpler preparation process and easier to achieve low-cost preparation of high-performance zirconium oxide powder.
[0004] However, in the actual process of preparing zirconium oxide powder by co-precipitation method, the agglomeration of precursor colloidal particles has always been a difficult problem. The agglomeration problem usually comes from two aspects. One is the agglomeration caused by adsorption between colloidal particles during precipitation, and the other is the agglomeration between precursor particles caused by the volatilization of solvent during drying. In order to solve these problems, more surfactants are usually added to the reaction solution to disperse the colloidal particles. However, too much surfactant will not only be difficult to remove completely in the subsequent calcination process, but also introduce additional impurity risks.
[0005] Therefore, there is a need for a zirconium oxide nanopowder and a preparation method thereof. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a zirconium oxide nanopowder and a preparation method thereof.
[0007] The present invention is achieved by a method for preparing a zirconium oxide nanopowder, comprising the following steps:
[0008] (1) mixing an inorganic zirconium salt, an inorganic yttrium salt and water to obtain a mixed solution A;
[0009] (2) mixing an inorganic alkaline precipitant with water and anhydrous ethanol in a certain proportion to obtain a mixed solution B;
[0010] (3) slowly adding the mixed solution A obtained in step (1) to the solution B in step (2) to perform a precipitation reaction to obtain a precipitate;
[0011] (4) filtering and washing the precipitate obtained in step (3);
[0012] (5) dispersing the precipitate obtained in step (4) in anhydrous ethanol, stirring and ultrasonically dispersing the precipitate until a colloidal liquid is formed;
[0013] (6) spray drying the colloid obtained in step (5) to obtain precursor particles with uniform particle size;
[0014] (7) The precursor particles obtained in step (6) are calcined at low temperature to obtain nano zirconium oxide powder.
[0015] Furthermore, the inorganic zirconium salt is zirconium oxychloride octahydrate, and the inorganic yttrium salt is yttrium chloride hexahydrate.
[0016] Furthermore, the inorganic alkaline precipitant is ammonium bicarbonate.
[0017] Another object of the present invention is to provide a method for preparing zirconium oxide nanopowder and prepare zirconium oxide nanopowder.
[0018] Another object of the present invention is to provide a zirconium oxide nanopowder, which is prepared by the following steps:
[0019] (1) mixing an inorganic zirconium salt and an inorganic yttrium salt with water to form a mixed solution A;
[0020] (2) mixing an inorganic alkaline precipitant with water and anhydrous ethanol to form a mixed solution B;
[0021] (3) slowly adding the mixed solution A to the mixed solution B to perform a precipitation reaction to obtain a precipitate;
[0022] (4) filtering and washing the precipitate to obtain a precipitate;
[0023] (5) dispersing the precipitate in anhydrous ethanol, stirring and ultrasonically dispersing the precipitate to obtain a colloidal solution;
[0024] (6) spray drying the colloidal liquid to obtain precursor particles;
[0025] (7) The precursor particles are calcined at low temperature to obtain zirconium oxide nanopowder.
[0026] Furthermore, the inorganic zirconium salt is zirconium chloride or zirconium nitrate, the inorganic yttrium salt is yttrium chloride or yttrium nitrate, and the inorganic alkaline precipitant is sodium hydroxide or ammonia water.
[0027] Furthermore, the spray drying process is controlled at a temperature of 80-120° C., and the particle size of the obtained precursor particles is uniformly distributed between 10-50 nanometers.
[0028] Furthermore, the temperature of the low-temperature calcination is 500-700° C., and the obtained zirconium oxide nanopowder has good crystallinity and a particle size uniformly distributed between 30-100 nanometers.
[0029] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0030] First, the present invention is simple and safe to operate, has low energy consumption, and can effectively solve the agglomeration problem of the prepared zirconium oxide powder. The present invention disperses the precipitated colloidal particles by adding anhydrous ethanol because the generated precipitated colloidal particles are insoluble in ethanol. This method can effectively avoid the appearance of agglomerates and will not introduce foreign impurities into the powder. In addition, the precursor is dried by spray drying, which can effectively avoid agglomeration during the drying process. In addition, the precursor prepared by the present invention only needs to be calcined at a relatively low temperature to obtain yttrium-stabilized zirconia powders of different crystal phases, which can effectively reduce the original crystal size and powder particle size of the powder, and is conducive to the preparation of high-purity, ultrafine, and uniform-particle-size zirconium oxide powders.
[0031] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are as follows: If the technical solution of the present invention can be successfully transformed, it will greatly improve the quality of domestic zirconia powder, shorten the gap with foreign powder, and promote the development of zirconia ceramic products.
[0032] The technical solution of the present invention fills the technical gap in the industry at home and abroad: the technical invention can effectively make up for the current situation of low product quality in the field of high-purity nano zirconium oxide powder in China.
[0033] The technical solution of the present invention solves a technical problem that people have been eager to solve but have never been successful: the technical solution of the present invention can effectively solve the problem of agglomeration of nanopowders during the preparation process, thereby obtaining monodisperse nanopowders.
[0034] Third, the technical solution of the present invention solves the technical problems faced in the existing zirconium oxide nanopowder preparation process, such as uneven particle size, insufficient purity, easy agglomeration during the preparation process, and low preparation efficiency, and has achieved significant technical progress, as shown in the following:
[0035] 1. Improve the uniformity of powder particle size: In the existing preparation process of zirconium oxide nanopowder, uneven particle size distribution is a common problem, which easily leads to unstable performance. The present invention controls the slow dripping speed of solution A and combines the introduction of anhydrous ethanol to significantly reduce the generation of large particles during the precipitation reaction, ensuring the uniform distribution of nanopowder particle size. The final zirconium oxide nanopowder maintains high uniformity at the nanoscale.
[0036] 2. Improve product purity: In the prior art, due to insufficient cleaning after precipitation, unreacted ions and by-products remain, which easily reduces the purity of the powder and affects its performance. The present invention effectively removes impurities and by-products during the precipitation, filtration and multiple washing processes, ensuring the purity of the precursor material, thereby preparing high-purity zirconium oxide nanopowder.
[0037] 3. Improve the problem of powder agglomeration: Zirconia nanopowder is prone to particle agglomeration during the preparation process, resulting in poor powder dispersibility and reduced performance. The present invention uses ultrasonic dispersion technology after precipitation to disperse the precipitate into anhydrous ethanol, ensuring that the nanoparticles can be evenly dispersed, avoiding the occurrence of agglomeration, thereby improving the dispersibility and application performance of the powder.
[0038] 4. Improve preparation efficiency and stability: In the traditional nano powder preparation process, due to the complex process and strict requirements on reaction conditions, it often leads to poor stability and low efficiency between batches. The present invention uses spray drying technology to quickly dry the evenly dispersed colloid into precursor particles with uniform particle size, which greatly improves the preparation efficiency of the powder, and in the subsequent low-temperature calcination process, further ensures the high crystallinity and batch stability of the nano powder.
[0039] 5. Meet the application needs of multiple fields: The high-purity, uniform-size zirconium oxide nanopowder prepared by the present invention has excellent thermal stability, mechanical strength and corrosion resistance, and is widely used in the fields of ceramic cutting tools, dental materials, fuel cells, high-temperature resistant coatings, etc. This high-performance powder solves the problem of insufficient performance of traditional materials under extreme conditions, and significantly improves the service life and performance stability of related products.
[0040] In summary, the technical solution of the present invention solves the key problems in the prior art by optimizing the preparation process in industrial applications, significantly improves the preparation quality and efficiency of zirconium oxide nanopowder, and promotes its widespread application in the field of high-end materials and technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a flow chart of a method for preparing zirconium oxide nanopowder provided in an embodiment of the present invention;
[0042] Figure 2is the XRD picture of the sample provided in Example 1 of the present invention;
[0043] Figure 3 is the XRD picture of the sample provided in Example 2 of the present invention;
[0044] Figure 4 This is a TEM image of the sample provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] like Figure 1 As shown, a method for preparing a zirconium oxide nanopowder provided by an embodiment of the present invention comprises the following steps:
[0047] (1) mixing an inorganic zirconium salt, an inorganic yttrium salt and water to obtain a mixed solution A;
[0048] (2) mixing an inorganic alkaline precipitant with water and anhydrous ethanol in a certain proportion to obtain a mixed solution B;
[0049] (3) slowly adding the mixed solution A obtained in step (1) to the solution B in step (2) to perform a precipitation reaction to obtain a precipitate;
[0050] (4) filtering and washing the precipitate obtained in step (3);
[0051] (5) dispersing the precipitate obtained in step (4) in anhydrous ethanol, stirring and ultrasonically dispersing the precipitate until a colloidal liquid is formed;
[0052] (6) spray drying the colloid obtained in step (5) to obtain precursor particles with uniform particle size;
[0053] (7) The precursor particles obtained in step (6) are calcined at low temperature to obtain nano zirconium oxide powder.
[0054] The method for preparing zirconium oxide nanopowder of the present invention uses multiple steps to precisely control the particle size and uniformity. First, in step (1), an inorganic zirconium salt and an inorganic yttrium salt are mixed with water to form a mixed solution A. Zirconium salt is a precursor material of zirconium oxide, and yttrium salt is usually used as a stabilizer in zirconium oxide powder to prevent its phase change at high temperature. This step ensures the uniform distribution of zirconium oxide and yttrium, laying the foundation for the uniformity of the subsequent precipitation reaction.
[0055] Next, in step (2), an inorganic alkaline precipitant is mixed with water and anhydrous ethanol to form a mixed solution B. The alkaline precipitant is usually sodium hydroxide or ammonia water, which is used to neutralize the zirconium and yttrium solutions to form insoluble precipitates. The addition of ethanol helps to improve the uniformity of the system and reduce the severity of the hydrolysis reaction, ensuring that the particle size of the precipitate is uniform.
[0056] In step (3), solution A is slowly added dropwise to solution B for precipitation reaction. In order to ensure the uniformity of the precipitation reaction, the addition speed of solution A is very important. Slow addition can prevent local reaction from being too fast to form large particle precipitation. By controlling the addition speed, it can be ensured that the precipitated particles are uniform and well distributed, which directly affects the quality of the final zirconium oxide powder.
[0057] In step (4), the precipitate generated by the reaction is filtered to remove the liquid phase, and washed multiple times to remove unreacted ions and by-products. The purpose of this step is to improve the purity of the precipitate, avoid the influence of impurities on the subsequent process, and ensure that a high-purity precursor precipitate is obtained.
[0058] Next, in step (5), the washed precipitate is dispersed in anhydrous ethanol and dispersed by stirring and ultrasonic treatment. The ultrasonic dispersion in this step can break up the agglomerates in the precipitate, so that the nano-scale particles can be redispersed into a stable colloidal liquid, ensuring that the particles remain uniform during the subsequent drying and calcination process.
[0059] Finally, in step (6) and step (7), the dispersed colloid is spray dried and then calcined at low temperature. Spray drying can convert the colloid into precursor particles with uniform particle size, while low temperature calcination can remove residual organic matter and moisture, and form nano zirconium oxide powder with good crystallinity. By controlling the calcination temperature, the particle size and structure of the powder are ensured to remain uniform, and the desired zirconium oxide nano powder is finally obtained.
[0060] Preferably, in step (1), the molar ratio of the inorganic zirconium salt to the inorganic yttrium salt is 100:(1-5).
[0061] Preferably, the inorganic zirconium salt in step (1) includes at least one of zirconium oxychloride and zirconium nitrate; and the inorganic yttrium salt includes at least one of yttrium nitrate and yttrium chloride.
[0062] Preferably, the concentration of zirconium ions in the mixed solution in step (1) is 0.1 to 3 mol / L.
[0063] Preferably, the concentration of the precipitant in step (2) is 0.1 to 5 mol / L.
[0064] Preferably, in step (2), the mass ratio of water to ethanol is 100:(1-20).
[0065] Preferably, the inorganic precipitant in step (2) includes at least one of ammonium bicarbonate and ammonium oxalate.
[0066] Preferably, the precipitation time in step (3) is 1 to 10 hours.
[0067] Preferably, the washing times in step (4) are not less than 2 times.
[0068] Preferably, in step (5), the volume ratio of the precipitate to anhydrous ethanol is 1:(1-20).
[0069] Preferably, the spray drying temperature in step (6) is 100-200°C.
[0070] Preferably, in step (7), the calcination temperature is 300-800° C., and the calcination time is 1-10 h.
[0071] Example 1
[0072] Step 1) dissolving zirconium oxychloride octahydrate and yttrium chloride hexahydrate in deionized water;
[0073] Step 2) dissolving ammonium bicarbonate and anhydrous ethanol in deionized water;
[0074] Step 3) adding the mixed solution in step 1) dropwise into the solution in step 2) and stirring to obtain a white colloidal precipitate;
[0075] Step 4) washing the white colloidal precipitate in step 3) with deionized water;
[0076] Step 5) mixing the precipitate washed in step 4) with anhydrous ethanol by volume, and stirring and ultrasonically dispersing the mixture;
[0077] Step 6) spray drying the precursor solution dispersed in step 5);
[0078] Step 7) calcining the precursor spray-dried in step 6) in a muffle furnace.
[0079] Example 2
[0080] Step 1) dissolving zirconium nitrate pentahydrate and yttrium chloride hexahydrate in deionized water;
[0081] Step 2) dissolving ammonium bicarbonate and anhydrous ethanol in deionized water;
[0082] Step 3) is the same as in Example 1;
[0083] Step 4) is the same as in Example 1;
[0084] Step 5) is the same as in Example 1;
[0085] Step 6) is the same as in Example 1;
[0086] Step 7) is the same as in Example 1.
[0087] The present invention can be successfully applied to the preparation of various oxide ceramic powders, effectively solve the agglomeration problem of oxide powders during the preparation process, and realize effective control of powder particle size.
[0088] The following are 6 specific industrial application examples of zirconium oxide nanopowder:
[0089] 1. Ceramic tool manufacturing
[0090] Zirconia nanopowder is widely used in the manufacture of high-performance ceramic cutting tools due to its extremely high hardness and wear resistance. These cutting tools not only have strong wear resistance, but also excellent corrosion resistance, and can maintain sharpness in various harsh cutting environments. They are widely used in the fields of mechanical processing and household appliances.
[0091] 2. Dental Materials
[0092] As a material with excellent biocompatibility, zirconia nanopowder is used to make dental restoration materials, such as crowns, bridges, etc. The strength and aesthetics of zirconia make it the first choice for high-quality dental restoration materials, which can replace traditional metal materials to achieve better appearance and comfort.
[0093] 3. Solid Oxide Fuel Cell (SOFC) Electrolyte
[0094] As an electrolyte material in solid oxide fuel cells, zirconia nanopowder is widely used due to its high ionic conductivity and good thermal stability. It can maintain stable electrochemical properties at high temperatures, thereby improving the efficiency and life of fuel cells, and is widely used in the field of clean energy.
[0095] 4. Biomedical implants
[0096] Zirconia nanopowder has good biocompatibility, corrosion resistance and mechanical strength, and is suitable for manufacturing biomedical implants, such as hip or knee replacement materials. The excellent properties of zirconium oxide materials enable it to maintain the stability and function of implants for a long time, reducing postoperative complications in patients.
[0097] 5. Mobile phone housing and high-end electronic equipment housing
[0098] Zirconia nanopowders are widely used in the manufacture of high-end mobile phone and electronic device casings due to their excellent strength and aesthetics. Compared with traditional metal and plastic materials, zirconia ceramic casings have higher scratch resistance and impact resistance while maintaining high finish and feel, improving the high-end quality of the product.
[0099] 6. High temperature resistant coating
[0100] Zirconia nanopowder is widely used in manufacturing high temperature resistant coatings due to its high melting point and good thermal stability. It is applied to the surface of parts in high temperature environments such as aerospace, automotive turbines, etc. This coating can effectively prevent oxidation and corrosion at high temperatures, extend the service life of key components, and improve the overall performance of the equipment.
[0101] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing zirconium oxide nanopowder, characterized in that: The following steps are involved: (1) mixing an inorganic zirconium salt, an inorganic yttrium salt and water to obtain a mixed solution A; (2) mixing an inorganic alkaline precipitant with water and anhydrous ethanol in a certain proportion to obtain a mixed solution B; (3) slowly adding the mixed solution A obtained in step (1) to the solution B in step (2) to perform a precipitation reaction to obtain a precipitate; (4) filtering and washing the precipitate obtained in step (3); (5) dispersing the precipitate obtained in step (4) in anhydrous ethanol, stirring and ultrasonically dispersing the precipitate until a colloidal liquid is formed; (6) spray drying the colloid obtained in step (5) to obtain precursor particles with uniform particle size; (7) The precursor particles obtained in step (6) are calcined at low temperature to obtain nano zirconium oxide powder.
2. The method for preparing zirconium oxide nanopowder according to claim 1, characterized in that: The inorganic zirconium salt is zirconium oxychloride octahydrate, and the inorganic yttrium salt is yttrium chloride hexahydrate.
3. The method for preparing zirconium oxide nanopowder according to claim 1, characterized in that: The inorganic alkaline precipitant is ammonium bicarbonate.
4. A zirconium oxide nanopowder prepared by the method for preparing zirconium oxide nanopowder according to any one of claims 1 to 3.
5. A zirconium oxide nanopowder, characterized in that: The zirconium oxide nanopowder is prepared by the following steps: (1) mixing an inorganic zirconium salt and an inorganic yttrium salt with water to form a mixed solution A; (2) mixing an inorganic alkaline precipitant with water and anhydrous ethanol to form a mixed solution B; (3) slowly adding the mixed solution A to the mixed solution B to perform a precipitation reaction to obtain a precipitate; (4) filtering and washing the precipitate to obtain a precipitate; (5) dispersing the precipitate in anhydrous ethanol, stirring and ultrasonically dispersing the precipitate to obtain a colloidal solution; (6) spray drying the colloidal liquid to obtain precursor particles; (7) The precursor particles are calcined at low temperature to obtain zirconium oxide nanopowder.
6. The zirconium oxide nanopowder according to claim 1, characterized in that: The inorganic zirconium salt is zirconium chloride or zirconium nitrate, the inorganic yttrium salt is yttrium chloride or yttrium nitrate, and the inorganic alkaline precipitant is sodium hydroxide or ammonia water.
7. The zirconium oxide nanopowder according to claim 1, characterized in that: The spray drying process is controlled at a temperature of 80-120° C., and the particle size of the obtained precursor particles is uniformly distributed between 10-50 nanometers.
8. The zirconium oxide nanopowder according to claim 1, characterized in that: The temperature of the low-temperature calcination is 500-700° C. The obtained zirconium oxide nanopowder has good crystallinity and a particle size uniformly distributed between 30-100 nanometers.